Systemic single administration of anti‐inflammatory microRNA 146a‐5p loaded in polymeric nanomedicines with active targetability attenuates neointimal hyperplasia by controlling inflammation in injured arteries in a rat model. Issue 9 (5th August 2022) - Sano, Masaya; Akagi, Daisuke; Naito, Mitsuru; Hoshina, Katsuyuki; Miyata, Kanjiro; Kataoka, Kazunori; Ishihara, Soichiro
Abstract: Neointimal hyperplasia (NIH) after revascularization is a key unsolved clinical problem. Various studies have shown that attenuation of the acute inflammatory response on the vascular wall can prevent NIH. MicroRNA146a‐5p (miR146a‐5p) has been reported to show anti‐inflammatory effects by inhibiting the NF‐κB pathway, a well‐known key player of inflammation of the vascular wall. Here, a nanomedicine, which can reach the vascular injury site, based on polymeric micelles was applied to deliver miR146a‐5p in a rat carotid artery balloon injury model. In vitro studies using inflammation‐induced vascular smooth muscle cell (VSMC) was performed. Results showed anti‐inflammatory response as an inhibitor of the NF‐κB pathway and VSMC migration, suppression of reactive oxygen species production, and proinflammatory cytokine gene expression in VSMCs. A single systemic administration of miR146a‐5p attenuated NIH and vessel remodeling in a carotid artery balloon injury model in both male and female rats in vivo. MiR146a‐5p reduced proinflammatory cytokine gene expression in injured arteries and monocyte/macrophage infiltration into the vascular wall. Therefore, miR146a‐5p delivery to the injury site demonstrated therapeutic potential against NIH after revascularization.